Using the Context, Input, Process and Product (CIPP) Model in the Evaluation of Training Programs - Khalif Ashhabul Umam; Iip Saripah (International Journal of Pedagogy and Teacher Education, 2018)
Evaluation of training program is made to establish the achievement of program objectives and to provide recommendations for program improvements. In this article, use of the CIPP (Context, Input, Process, and Product) evaluation model in training programs is discussed. It is an evaluation research, with a descriptive quantitative approach involving 16 training program participants as research subjects. The data collection techniques were based on questionnaires as the main instrument, with interview guides and observation guidelines as supporting instruments. The data analysis was made by comparing the scores obtained with the ideal score and multiplying by 100%; the results of these calculations were then grouped into a number of criteria that had been established. The results of the study indicate that the context dimension consisting of training objectives, training needs assessment, and state agency program organizers obtained a PE (Percentage of Effectiveness) score of 75.04%, placing it in the "fair" criterion. In the input dimension, consisting of participant description , instructor condition, infrastructure, training curriculum and instructional media, the PE score was 79.44% again in the "fair" criterion. In the process dimension, comprising lecture method, discussion method, demonstration method, question and answer method, practice method, field visiting method and evaluation of learning outcomes, the PE score obtained was 78.75%, which was also in the "fair" criterion. Finally, in the product dimension of knowledge aspect, attitude aspect and skill aspect, the PE score was 82.29%, in the “good" criterion. Based on the results of the dimension evaluation, the total PE score obtained was 78.88%, or overall in the "fair" criterion. It can be concluded that in general the execution of this training program was successful, so it is recommended that similar programs be conducted again, with some improvements.